Some Aspects Of The Life Cycle Of Fish Blood Fluke, Sanguinicola Armata Plehn, 1905 (Digenea: Sanguinicolidae) In Grass Carp (Ctenopharyngodon Idellus Cuvler And Valenciennes, 1884) Fingerlings - Kua, Beng Chu (1995)

(untitled)
The life - cycle of the fish blood fluke , Sanguinicola armata Plehn , 1905 was studied in the laboratory . The snail Gyraulus convexiusculus Hutton , 1849 was identified as the intermediate host of S. armata from grass carp ( ctenopharyngodon idellus ) finger lings. Two types of experiment ( pre-trial and laboratory experimental infections ) were carried out in order to infect the laboratory bred snails. The pre -trial study was divided into three experiments. In the firs texperiment , twenty infected fish were exposed to the thirty uninfected snail sand was left for the duration of the experiment. For the second experiment , similar number of fish and snails were left together for 24 hours.